Fear in modern Iraqi Poetry (The poet Abd al-Razzaq Abd al-Wahed as a model) (Texas Journal of Philology, Culture and History, 2023)
The literary phenomenon is the subject of a study when it organizes the literary production: poetry or artistic prose and requires extrapolation and research. This phenomenon, whose circle has widened in Iraqi poetry in general, and in the poetry of the poet Abd al-Razzaq Abd al-Wahed in particular, whose poetry spanned two centuries. His poetry was the witness of a literary era that extended to broad poetic generations. This is the first reason for the selection. The second reason: the quality of his poetry and the abundance of his poetic production. The third reason: it is that this phenomenon percolates in his poetry and contained in his poetic collections from the beginnings and remained present and was a source of form and content for many of his poems. This study tried to shed light on fear linguistically and idiomatically, and it was procedural based on dividing it into the types of fear that the study extrapolated, so it was: political fear first, fear of death second, then fear of gray hair and old age third, and fear of love and its disappointments fourth, accompanied by poetic texts that represented these four types .